PERANCANGAN SISTEM INFORMASI UNTUK KONFIGURASI PERANGKAT JARINGAN BERBASIS WEB : Studi Kasus PT. Indonesia Comnets Plus - Novalino Reynaldi Anas (2020)
In the industrial era 4.0 the role of the Internet network is very underlying in the company's business activities. If the internet network is damaged, of course, the entire business process of a company will be hampered and cause harm to the company. To reduce these impacts, PT.Indonesia Comnets Plus recruits professional workers who have been certified as Network Engineers so that the work carried out is effective and minimizes damage. But in the field, a problem was found that the technician could not memorize the configuration in detail, thus slowing his work. Therefore, an Information System Design for Web-Based Network Device Configuration was formed that could assist field technicians in configuring network devices without having to open modules and type in each configuration command. In developing systems, development methods are needed that are accurate to the needs of the user. Therefore, the Prototyping method was chosen as the method used because it can describe the real needs of users.